STAKEHOLDERS ANALYSIS OF MANGROVE ECOSYSTEM MANAGEMENT IN SEGARA ANAKAN LAGOON, CILACAP - Ardiyanto, Anjalli Tasha; Hilmi, Endang; Mahdiana, Arif; Junaidi, Teuku; Prayogo, Norman Arie; Dewi, Rose; Cahyo, Tri Nur (Indonesian Journal of Forestry Research, 2024)
The mangrove ecosystems are one type of coastal ecosystem found along coastlines and river estuaries that are influenced by tides and inundation. Segara Anakan Lagoon, Cilacap as one type of coastal ecosystem has a protection function, coastal area buffer, and cultivation area function that must be supported from the aspects of policy and institutions, communication, and coordination. This study aims to identify the role of stakeholders and the relationship between stakeholders in mangrove ecosystem management in Segara Anakan Lagoon, Cilacap. The research method used was a survey and interview method analyzed with MACTOR software. The results showed that there were 18 stakeholders who involved in mangrove ecosystem management in Segara Anakan Lagoon, Cilacap. The stakeholders are classified into main stakeholders, key stakeholders, and supporting stakeholders using the objective of mangrove management as key activities such as silvofishery, mangrove conservation, fishing activity, industry activity, etc. The level of convergence between stakeholders was 96.1% and the level of divergence was 3.9%. These results indicate a relatively low potential for conflict between stakeholders. The research can be used as a model relation between stakeholders to support the management activity of Segara Anakan Lagoon.